Active learning: a model from the formative experience from the student exchange of I, II and III level of theoretical and methodological courses of the School of Sociology of the National University and the community of Cacho Negro, Sarapiquí - Barrantes Arrieta, Andrea (2025)
This article describes an active learning methodology that involved 120 students from the School of Sociology at the National University of Costa Rica and the community of Cacho Negro, with the aim of deepening the application of theoretical and practical knowledge of the social sciences in a real-world context. The methodology, implemented in two theoretical courses and one practical course, sought to empower students and modify the approach to content and assessment. The results indicate a greater deepening of curricular knowledge and the development of socially sensitive competencies, skills, and attitudes. The study concludes that education should be an instrument of social transformation, which implies the need to break with traditional structures, make critical adjustments, and reimagine assessment as a horizontal process of growth, leaving aside the idea of hierarchy. Ultimately, the article highlights that the challenge is to innovate in order to achieve a more inclusive and effective education that privileges freedom of thought and critical reflection.